Gas-liquid flow regimes in horizontal annulus - Eyo, Edem Nsefik; Lao, Liyun (Elsevier, 2018)
Gas-liquid flows in annulus channels are frequently encountered in the underbalanced drilling operation when the gasified drilling fluid is used. Accurate characterization of two-phase flow regimes in such conduits is critically important in order to gain a better understanding of the flow behaviours in the channels, thus to ensure a successful drilling operation achieved. In this paper experimental studies regarding gas-liquid flows in a concentric and fully eccentric horizontal annulus were reported. The test section setups of the flow loop have a length of 10.8 m, with outer and inner pipe diameters of 0.0768 m and 0.060 m respectively. Air and water at atmospheric pressure constituted the gas and liquid phases and the range of gas and liquid superficial velocities investigated during this study was 0.14–24 m/s and 0.15–2.78 m/s respectively. Flow regimes observed in both annulus setups by high speed camera imaging were dispersed bubble, elongated bubble, slug, wavy slug, churn, wavy annular and annular. A detailed description of the flow regimes with different features are presented together with high quality images. The local liquid holdup time series together with its probability density function (PDF) are used to gain more insights about the characteristics of the observed flow regimes. Effects of the annulus eccentricity on the observed flow regimes are also investigated. It is found that the annulus eccentricity affects the shape and structure of the elongated bubble, wavy annular and annular flow regimes. It is also observed that the annulus eccentricity causes the transition from elongated bubble to dispersed bubble to take place at higher liquid superficial velocities. It is also found that in the fully eccentric annulus causes transitions between different flow regimes to occur at higher liquid and lower gas superficial velocities when compared with that of concentric ones. An improved flow regime map is proposed based on gas and liquid Froude numbers by integrating the test results from this study with over 1000 data points found in literature.
Keywords: Concentric; Fully eccentric; Two-phase flow; Annulus; Horizontal; Experimental